Meaning of the Bedhaya Tirta Ritual Dance Form in the Odalan Ceremony of Tirta Empul Temple Surabaya - I Nengah, I Nengah Mariasa; Sekti, Retnayu Prasetyanti Sekti; -, Enie wahyuning Handayani; I Gede, I Gede Dharma Utamayasa (Jurnal Seni Tari, 2025)
The odalan ritual of the Tirta Empul Surabaya temple is held once a year, every month of Purnama Kasa. Since 2017, every temple odalan event has presented the Bedhaya Tirta ritual dance. The dance delivers five main dancers dressed in green, and the presentation involves the ritual of pouring tirta (holy water). This research aims to describe the form and meaning of the Bedhaya Tirta ritual dance in the odalan of Tirta Empul Temple, Surabaya. This research used an ethnochoreological approach and Pierce's semiotics in qualitative research. Specifically, the form of dance movements was studied through pure and meaningful movements. Data were collected by observation, interviews, and document studies. Bedhaya Tirta dance is a choreography in the form of a ritual full of meaning. Iconically, this dance work is an imaginative manifestation of the combination of God and Goddess in the holy water dance. Symbolically, it contains the meaning of prosperity. The index explains that the grace of sacred prosperity was present at Tirta Empul Temple when performing the Bedhaya Tirta dance. The solanugerah movement as a sign means that at the time the performance takes place, the tirta puruṣa descends from akasa (space) and the tirta pradhāna waits on pertiwi (earth), then unites into holy water called tirta ardhanareswari. The conclusion is that the Bedhaya Tirta dance is a ritual dance for the presence of the holy water for spiritual well-being at the Tirta Empul Babatan Temple, Surabaya.